Managing the cultural diversity in the workplace In the hospitality industry - Tran, Khanh Ngoc (2020)
The dissertation investigates cultural diversity in the hospitality management. The purpose of this paper is to present effective ways to improve cultural diversity in a workplace by analyzing the opportunities and problems of cultural diversity, investigating the current status of the cultural diversity management, and exploring solutions feasible in managing cultural-diversity issues. This study was commissioned by four International five-star hotels in Hanoi as InterContinental Hanoi Westlake andSheraton Hanoi Hotel, Sofitel Plaza Hanoi, and Hotel Pullman Hanoi.